Education for All : Including Children with Disabilities - Peters, Susan (World Bank, Washington, DC, 2012)
An estimated 40 million of the 115 million children out of school have disabilities. The vast majority of these children have moderate impairments that are often not visible or easily diagnosed. Disabled children include those with learning difficulties, speech difficulties, physical, cognitive, sensory and emotional difficulties. Children with disabilities are likely to have never attended school. A 1991 report by the UN Rapporteur on Human Rights and Disabilities found that at least one in ten persons in the majority of countries has a physical, cognitive, or sensory (deaf/blind) impairment. Fewer than 5 percent are believed to reach the "Education For All" goal of primary school completion. This number may be growing due to global conditions of increasing poverty, armed conflict, child labor practices, violence and abuse, and HIV/AIDS. Because these children are part of a family unit, it is estimated that at least 25 percent of the world population is directly affected by the presence of disability.